2010
DOI: 10.1038/ejhg.2009.231
|View full text |Cite|
|
Sign up to set email alerts
|

Human Y chromosome haplogroup R-V88: a paternal genetic record of early mid Holocene trans-Saharan connections and the spread of Chadic languages

Abstract: Although human Y chromosomes belonging to haplogroup R1b are quite rare in Africa, being found mainly in Asia and Europe, a group of chromosomes within the paragroup R-P25* are found concentrated in the central-western part of the African continent, where they can be detected at frequencies as high as 95%. Phylogenetic evidence and coalescence time estimates suggest that R-P25* chromosomes (or their phylogenetic ancestor) may have been carried to Africa by an Asia-to-Africa back migration in prehistoric times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
119
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 44 publications
7
119
2
Order By: Relevance
“…3,5,[18][19][20][21][22] Moreover, eight additional SNPs inside haplogroup R1b were also included in our set to increase the resolution of this haplogroup. 7 A hierarchical approach (Supplementary Figure S1) based on the phylogeny reported by Karafet et al 17 and M213 carried the derived allele, Multiplex 2 (described by Brió n et al 23 ) was performed under the same conditions used for the other three multiplexes; (ii) in chromosomes carrying the derived allele at marker P25, M269 was typed using the RFLP technique. The amplification PCR for this marker was conducted using the primers described by Beleza et al, 18 and the conditions were optimised from Gomes et al 3 for the multiplexes used.…”
Section: Y-snp Typingmentioning
confidence: 99%
See 4 more Smart Citations
“…3,5,[18][19][20][21][22] Moreover, eight additional SNPs inside haplogroup R1b were also included in our set to increase the resolution of this haplogroup. 7 A hierarchical approach (Supplementary Figure S1) based on the phylogeny reported by Karafet et al 17 and M213 carried the derived allele, Multiplex 2 (described by Brió n et al 23 ) was performed under the same conditions used for the other three multiplexes; (ii) in chromosomes carrying the derived allele at marker P25, M269 was typed using the RFLP technique. The amplification PCR for this marker was conducted using the primers described by Beleza et al, 18 and the conditions were optimised from Gomes et al 3 for the multiplexes used.…”
Section: Y-snp Typingmentioning
confidence: 99%
“…[2][3][4] Apart from the aforementioned haplogroups, some studies have reported unexpectedly high frequencies of haplogroup R1b1-P25 in some African populations. [5][6][7] This haplogroup is thought to have originated in Europe, and its high frequencies in Central-West African countries have been explained through a migration back to Africa in prehistoric times, mediated in Africa by speakers of the Chadic family of Afro-Asiatic languages. 6,7 The arrival of this ethnic group to Lake Chad from the Proto-Afro-Asiatic homeland in Eastern Africa has been explained by two different hypotheses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations